The Early Stages of Workplace Bullying and How It Becomes Prolonged: The Role of Culture in Predicting Target Responses - Samnani, Al-Karim (2013)
The extant workplace bullying literature has largely overlooked the potential role of culture. Drawing on cognitive consistency theory, culture’s influence on targets’ reactions toward subtle forms of bullying during its early stages is theorized. This theoretical analysis proposes that employees high in individualism and low in power distance are more likely to engage in resistance-based responses toward subtle acts of bullying than employees high in collectivism and power distance, respectively. Targets’ resistance-based responses, which are also influenced by learned helplessness deficits, along with perpetrator revenge behaviors, influence whether bullying becomes prolonged. A number of testable propositions are offered based on the conceptual model presented. Theoretical and practical implications are discussed and avenues for future research are offered.
Keywords: Subtle bullying; Culture; Bullying responses; Workplace bullying